2016
DOI: 10.1093/mnras/stw3248
|View full text |Cite
|
Sign up to set email alerts
|

Probing the primordial Universe with MeerKAT and DES

Abstract: It is usually assumed that we will need to wait until next-generation surveys like Euclid, LSST and SKA, in order to improve on the current best constraints on primordial non-Gaussianity from the Planck experiment. We show that two contemporary surveys, with the SKA precursor MeerKAT and the Dark Energy Survey (DES), can be combined using the multi-tracer technique to deliver an accuracy on measurement of f NL that is up to three times better than Planck.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…Intensity mapping surveys may also be helpful because they can add high redshift information (e.g. see [93] for f NL ). On the CMB side, it would be interesting to study how close the Simons Observatory [4] in combination with pre-LSST LSS surveys can get to the CMB-S4/LSST forecasts presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity mapping surveys may also be helpful because they can add high redshift information (e.g. see [93] for f NL ). On the CMB side, it would be interesting to study how close the Simons Observatory [4] in combination with pre-LSST LSS surveys can get to the CMB-S4/LSST forecasts presented here.…”
Section: Discussionmentioning
confidence: 99%
“…A strong effort in forecasting the possible imprint of primordial non-Gaussianity in LSS has been pushing the limits to order O(1) for local-type non-Gaussianities 14 and O(10) for equilateral and orthogonal ones [16,19,21,30,280,281,285,343,. Several future surveys such as SPHEREx [16], Euclid [408], MeerKAT+DES [411] and SKA [19] might achieve these limits. and we used Bayes' theorem to write N (ν, J 1 ) = N (ν) N (J 1 |ν) and consequently written the conditional gaussian distribution P G (x − µ; s) with shifted mean µ = γ 1 ν and variance s = 1 − γ 2 1 .…”
Section: Observational Prospectsmentioning
confidence: 99%
“…Cosmic variance can be beaten down using multiple tracers, and this is applied to MeerKAT and DES in [18]. It is shown that the multi-tracer technique can achieve errors on f NL better than those of Planck, even with a conservative assumption on the overlap sky area between MeerKAT and DES (3,000 or 4000 deg 2 ), and with a maximum of 4000 hr integration time (σ ( f NL ) ∼ 3.6 in L-band and 2.3 in UHF).…”
Section: Multi-tracer Constraints On Primordial Non-gaussianitymentioning
confidence: 99%